Britain and Hong Kong: the 2019 protests and their aftermath. Issue 2 (7th January 2021) - Summers, Tim
Abstract : Purpose: The purpose of this paper is to examine British policy towards Hong Kong from the protests of 2019 through political controversies in 2020. Design/methodology/approach: The paper offers a foreign policy analysis based on a chronological account of the public interventions made by London from April 2019 to the passage of the national security law in the middle of 2020. It discusses the factors which contributed to the UK's positions and looks in more detail at an issue which relates to the British colonial legacy: the status of British National (Overseas) passport holders. Findings: The paper argues that the UK's policy was influenced by a combination of factors: developments in Hong Kong, the implications of and perceptions about its historical position as the former colonial power, the growing influence of lobby groups in the UK and Hong Kong (especially in agenda setting), and (to a lesser extent) the UK's wider relations with China. In trying to balance these, British policy tended to be reactive rather than strategic. London generally took positions sympathetic to the protest movement and political opposition, characterised in the paper as "soft partisanship", shifting to clear opposition to Beijing's approach when the National Security Law was announced. Social implications: The paper helps to understand international policy towards Hong Kong. Originality/value: The paper offers the first account of British policy towards Hong Kong during this period and adds to the limited existing literature on the UK's Hong Kong policy over recent years. This case study sheds light on wider questions of international perceptions of developments in Hong Kong during a tumultuous period in the city's history and informs broader studies of foreign policymaking.